Baby senses - Stoppard, Miriam; Kind, Dave (London : DK, 2007)
Simple text and colorful photographs on textured pages introduce the five senses.
Cover title.
On board pages.
Spiral-bound.
2.2
K-3
Keywords: Senses and sensation -- Juvenile fiction; Senses and sensation -- Fiction; Board books for children, English; Senses and sensation -- Fiction